Respuesta :

Answer:

[tex]f'(x)=4e^{4x} -4e^{-4x}[/tex]

Step-by-step explanation:

To find this derivative, we will need to use the chain rule.

As there is a variable in the exponent we can use this formula:

[tex]f'(x)=u'e^u[/tex]

In this case, [tex]u=4x[/tex] and [tex]u=-4x[/tex]

This means that [tex]u'=4[/tex] and [tex]u'=-4[/tex] respectively

This gives us [tex]f'(x)=4e^{4x} -4e^{-4x}[/tex]

Answer:

Step-by-step explanation:

note : (e^(u(x))' = (u(x))'e^(u(x)

f(x)= e^(4x) + e^-(4x)

f'(x) =4e^(4x) - 4 e^-(4x)